2001
DOI: 10.1103/physrevb.64.235402
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon resonances of silver nanowires with a nonregular cross section

Abstract: We investigate numerically the spectrum of plasmon resonances for metallic nanowires with a nonregular cross section, in the 20-50 nm range. We first consider the resonance spectra corresponding to nanowires whose cross sections form different simplexes. The number of resonances strongly increases when the section symmetry decreases: A cylindrical wire exhibits one resonance, whereas we observe more than five distinct resonances for a triangular particle. The spectral range covered by these different resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
338
1
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(361 citation statements)
references
References 79 publications
15
338
1
7
Order By: Relevance
“…In this case, the strength of the Raman signal was intermediate between parts a and c of Figure 3. These results are in accordance with the polarization dependence calculated for the SERS from individual metallic nanowires 19 and from periodic silver structures (silver gratings). 23 In all these cases, the electrons in the conductor are only spatially confined in the nanometric range along the direction perpendicular to the main axis of the structures, and the surface plasmons can then only be excited when the polarization vector of the light field are oriented at the same direction.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In this case, the strength of the Raman signal was intermediate between parts a and c of Figure 3. These results are in accordance with the polarization dependence calculated for the SERS from individual metallic nanowires 19 and from periodic silver structures (silver gratings). 23 In all these cases, the electrons in the conductor are only spatially confined in the nanometric range along the direction perpendicular to the main axis of the structures, and the surface plasmons can then only be excited when the polarization vector of the light field are oriented at the same direction.…”
Section: Resultssupporting
confidence: 89%
“…19 These calculations showed that the SP resonances are highly localized at the tips of the nanostructures; consequently, the number of SP resonances per nanowire increases as the overall symmetry of the particle's cross section decreases. 19 The sharp tips and narrow channels presented within the substructures in Figure 2 should be ideal for the production of highly localized SP resonances and, consequently, SERS. Figure 3 shows the surface-enhanced Raman spectra from oxa dye adsorbed on the nanostructured gold surface (shown in Figure 2) obtained in the forward scattering geometry (using the experimental setup shown in Figure 1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is mainly because that the symmetry of the nanowires improves. It is consistent with the reported theory that the number of SPR peaks usually decreases with the increasing symmetry of nanowires [28]. In order to investigate the features of LiFePO 4 and LiFePO 4 /Ag nanowires cathodes, these cathodes are analyzed with XRD, FSEM and energy-dispersive X-ray spectroscopy (EDX).…”
Section: Measurementsmentioning
confidence: 56%
“…Figures 8 and 9 show the field distributions of E Z for 1D gold nanogratings with a period of 100 nm, a width of 50 nm, and a thickness of 10 nm. The figures present well-known features of LSPs excited at a metallic nanostructures that are quite typical of the fields of nonregular metallic nanostructures [44]. On the assumption of an incident electric field of unit amplitude, maximum field amplitudes obtained by FDTD were E X = 59, H Y = 8, and E Z = 41.…”
Section: Periodic Nanostructure-based Lspr Biosensorsmentioning
confidence: 81%